Measurement of Neutrophil Gelatinase-Associated Lipocalin Concentration in Canine Cerebrospinal Fluid and Serum and Its Involvement in Neuroinflammation - Meyerhoff, Nina; Rohn, Karl; Carlson, Regina; Tipold, Andrea (Frontiers in Veterinary Science, 2019)
Neutrophil gelatinase-associated Lipocalin (NGAL) is a glycoprotein involved in inflammation acting as an acute phase protein and chemokine as well as a regulator of iron homeostasis. NGAL has been shown to be upregulated in experimental autoimmune encephalomyelitis (EAE) in mice. Increased NGAL concentration in cerebrospinal fluid (CSF) and expression in central nervous system (CNS) has been described in human neuroinflammatory disease such as multiple sclerosis and neuropsychiatric lupus as well as in bacterial meningitis. We aimed to investigate involvement of NGAL in spontaneous canine neuroinflammation as a potential large animal model for immune- mediated neurological disorders. A commercially available Enzyme-linked Immunosorbent Assay (ELISA) for detection of canine NGAL was validated for use in canine CSF. Concentration in CSF and serum of canine patients suffering from steroid- responsive meningitis- arteriitis (SRMA), Meningoencephalitis of unknown origin (MUO), different non- inflammatory CNS disease and control dogs were compared. Relationship between NGAL concentration in CSF and serum and inflammatory parameters in CSF and blood (IgA concentration, total nucleated cell count (TNCC), protein content) as well as association with erythrocytes in CSF, duration of illness, plasma creatinine and urinary leucocytes were evaluated. In dogs with SRMA and MUO, CSF concentration of NGAL was significantly higher than in dogs with idiopathic epilepsy, compressive myelopathy, intracranial neoplasia and SRMA in remission (p < 0.0001). Patients with acute SRMA had significantly higher levels of NGAL in CSF than neurologically normal controls (p < 0.0001). Serum NGAL concentrations were significantly higher in dogs with SRMA than in patients with myelopathy and intracranial neoplasia (p < 0.0001). NGAL levels in CSF were strongly positively associated with IgA concentration (rSpear= 0.60116, p < 0.0001), TNCC (rSpear= 0.65746, p < 0.0001) and protein content (rSpear= 0.73353, p< 0.0001) in CSF. It can be measured in CSF of healthy and diseased dogs. Higher concentrations in canine patients with SRMA as well as positive association with TNCC in CSF suggest an involvement in pro- inflammatory pathways and chemotaxis in SRMA. High serum levels of NGAL in serum of SRMA patients in different stages of disease might reflect the systemic character of the disease.